A pecuária leiteira na microrregião geográfica de Ituiutaba (MG): atuação dos sujeitos da cadeia produtiva do leite - Souto, Thales Silveira (2021)
Dairy farming is an important activity of the Brazilian economy. However, there are difficulties that dairy farmers stand up to, as well as their low valuation in relation to others productive sectors. Considering these concerns, the study problem focused on the dairy production scenario in the municipalities of the Geographic Microregion of Ituiutaba (MRG-017), that is composed of Cachoeira Dourada, Capinópolis, Gurinhatã, Ipiaçu, Ituiutaba and Santa Vitória. The general objective of the research was to analyze the importance of the production of dairy cattle for the socio-spatial organization of the municipalities of MRG-017, from 1977 to 2017, investigating the perspectives and challenges that dairy farmers are experiencing. And, specifically, we sought to: (a) Identify public policies and private actions that stimulate the production of dairy cattle at MRG-017; (b) Verify the importance of dairy farming for the commercial agricultural establishments of MRG-017; (c) Analyze the dairy production scenario in the focused territorial units to know the perspectives and challenges for the development of this sector and (d) Understand the reality faced by the dairy farmer and its perspectives as the main actors/subjects of this supply chain. The methodological pathway was organized in four stages: the bibliographic review, the collection of secondary data, the interviews with several agencies responsible for assisting and supporting rural production, such as dairy processors and collectors, with agricultural commercial establishments and with dairy farmers and, the last step, it was made the analysis and interpretation of the information. It was found that this production has different degrees of development, because the articulation of the sector allowed greater intensity in Ituiutaba and Santa Vitória, due to the presence of dairy industries and dairy collectors in these municipalities, as well as in Gurinhatã, due to the closeness to the aforementioned municipalities. Cachoeira Dourada, Capinópolis and Ipiaçu have lower participation, because the aptitude of the farmers, linked to the performance of the agencies and institutions of support and agricultural assistance, are focused on beef cattle and agriculture, especially soybean and sugarcane. However, it becomes evident that in the analyzed time frame there was an increase in dairy productivity, especially in Ituiutaba, Santa Vitória and Gurinhatã, as a result of the use of technologies. The increase in productivity is based on investment, forgetting on the sidelines the farmers who are unable to capitalize. Although in the farming productive scenario the expansion of agriculture is taking place, it is noteworthy that dairy production is an alternative, compared to the expansion of soybean and sugarcane, establishing itself, therefore, in the sphere of resistance against the expansion of monocultures. There was a need to organize policies that match with producers' reality, within the importance of appreciation of this activity, through the fair price paid per liter of milk, as well as its stability. Based on these reflections, it is noteworthy that in Gurinhatã, Ituiutaba and Santa Vitória there is a greater production, meeting the needs of processors and milk collectors in the microregion, generating tax, employment and income, boosting the economy. However, there are challenges in the daily life of the dairy farmer, making it difficult to develop this production.